Pemanfaatan Panel Surya Untuk Pompa Irigasi Tanaman di Area Perhutani Jatirejo Cepu - Asepta Surya Wardhana; Ayende, Ayende; Pujianto, Pujianto; Roni Heru Triyanto; Astrie Kusuma Dewi (Yayasan Literasi Sains Indonesia, 2023)
Indonesia is an agricultural country with a broad forest area with agricultural areas everywhere and evenly distributed. The Cepu Subdistrict area has fairly broad and has not been fully utilized maximally. The main priority faced by consistent water needs to maintain soil fertility. Solution This need is needed a good irrigation system during the dry season. Conventionally the use of diesel water pumps with fuel for agricultural irrigation systems is needed expensive and ineffective. The utilization of solar power for water pumps is one of the alternatives to reliable, efficient, effective, and efficient solutions to keep the irrigation system running well during the dry season. This service has successfully implemented the use of solar panels of 200WP to run a submersible pump with a depth of ± 4 meters infiltration well. This applied technology uses a timer automation system that runs pump performance during the day. For irrigation systems, implement an automation system in water with 2: 1 where 2 hours of watering and 1-hour filling water reservoir. This application can improve the planting results from farmers around Perhutani land. The land that is originally difficult with water will guarantee the water needs during the dry period.